Penggunaan model pembelajaran problem based learning (PBL) untuk meningkatkan pemahaman konsep IPA pada siswa kelas V SD - Lutpiah, Siti; Pratama, D. Fadly; Wulandari, Medita Ayu (IKIP Siliwangi, 2024)
Abstract Students' lack of activeness in expressing their opinions is the background of research on concept understanding in science learning in grade V elementary school. The research objectives were to investigate and analyze: (1) Knowing the improvement of the concept understanding ability of fifth grade elementary school students through the use of the Problem Based Learning learning model, (2) knowing the difficulties of fifth grade students in improving the ability to understand science concepts, (3) knowing the difficulties of teachers in improving the ability to understand concepts by applying the Problem Based Learning learning model. The research method used is mix method with sequential explanatory design. The sample of this study was fifth grade students of SDN 1 Karangtanjung, which amounted to 25 students and consisted of 7 male students and 18 female students. The instrument used in the research was 15 questions, and non-test instruments in the form of surveys, observations, and interviews. Analyze data taken from pretest, posttest and N-gain scores which are then processed using SPSS 16 and Microsoft Excel. The results showed an improved ability to comprehend students' concepts after being used the Problem Based Learning model. Keyword: Concepts Understanding Ability, Model Problem Based Learning Abstrak Kurangnya keaktifan siswa dalam menyampaikan pendapatnya melatarbelakangi penelitian mengenai pemahaman konsep IPA di kelas V SD. Penelitian ini bertujuan untuk memahami dan menelaah: (1) Mengetahui peningkatan kemampuan pemahaman konsep siswa kelas V SD melalui penggunaan model pembelajaran Problem Based Learning, (2) mengetahui kesulitan siswa kelas V dalam meningkatkan kemampuan pemahaman konsep IPA, (3) mengetahui kesulitan guru dalam meningkatkan kemampuan pemahaman konsep dengan menggunakan model pembelajaran Problem Based Learning. Metode penelitian yang digunakan adalah mix methode dengan desain sequential explanatory. Sampel penelitian ini merupakan siswa di kelas V SDN 1 Karangtanjung yang berjumlah 25 orang siswa dan terdiri dari 7 orang siswa laki-laki serta 18 orang siswa perempuan. Instrumen tes digunakan dalam penelitian berupa 15 soal uran, serta instrumen non-tes berupa angket, observasi, dan wawancara. Analis data diambil dari skor pretest, posttest serta N-gain yang lalu diolah menggunnakan SPSS 16 dan microsoft excel. Kesimpulan dari hasil analisis yang diperoleh adalah terdapatnya peningkatan kemampuan pemahaman konsep dasar siswa dengan menggunakan model Problem Based Learning. Kata Kunci: Kemampuan Pemahaman Konsep, Model Problem Based Learning